Application of Konjac Glucomannan with Chitosan Coating in Yellow Alkaline Noodles - Shishuai Wang; Jiaxin He; Shanshan Huang; Bin Li (Foods, 2023)
To improve the quality of the characteristics of yellow alkaline noodles and enrich their nutritional value, konjac glucomannan (KGM) with or without chitosan coating were added to noodles, and their application effects were investigated in terms of color, texture, water absorption, starch digestion, total plate count (TPC) and microstructure. Chitosan–konjac glucomannan (CK) complex was firstly prepared by embedding konjac powder with chitosan sol. After embedding, the hydrophilicity of KGM decreased significantly. Then, either CK or native KGM were mixed evenly with flour before saline water, and soda was subsequently added to produce noodles. Compared with native KGM, CK provided the noodles with a higher brightness and a lighter yellow color. In terms of texture properties, although the firmness of CK noodles was weaker than that of KGM noodles, the tensile properties were enhanced. After embedding, the water absorption of CK noodles decreased and the content of resistant starch (RS) in the noodles increased. During storage, the TPC in CK noodles was significantly lower than that in KGM noodles. At a CK content of 5%, the noodles presented a lightness of 87.41, a b value of 17.75, a shear work of 39.9 g·cm, a tensile distance of 84.28 cm, a water absorption of 69.48%, a RS content of 17.97% and a TPC of 2.74 lg CFU/g at 10 days. In general, KGM with chitosan coating could improve the physicochemical qualities of noodles and extend their shelf life to a certain extent.